869. Evaluation of Broad-Spectrum Antibiotic De-Escalation in Patients with Health-Care Associated Pneumonia (HCAP) and No Microbiological Diagnosis. (26th November 2018) - Patel, Twisha S; Petty, Lindsay; Conlon, Anna; Eschenauer, Gregory; Nielsen, Daniel; Vaughn, Valerie; Kaye, Keith S; Malani, Anurag; Osterholzer, Danielle; Thyagarajan, Rama; Flanders, Scott; Gandhi, Tejal N
Abstract: Background: Broad-spectrum (BS) antibiotics directed against Pseudomonas aeruginosa and methicillin-resistant Staphylococcus aureus (MRSA) are commonly used for health-care associated pneumonia (HCAP) treatment. Many patients with HCAP do not have a microbiologically confirmed diagnosis. The goal of this study was to evaluate the impact of antibiotic de-escalation on clinical outcomes in patients with HCAP without a microbiological diagnosis. Methods: This is a retrospective cohort study of adult, non-ICU, medical patients hospitalized with HCAP between January 2016 and February 2018 at 46 Michigan hospitals. Exclusions included extrapulmonary infection, severe immune suppression, or clinical instability on day 4. Included patients: (1) lacked any positive culture (blood/sputum); (2) started on empiric anti- P. aeruginosa and anti-MRSA therapy by hospital day 2; (3) switched to a narrow-spectrum (NS) regimen (no anti- P. aeruginosa or anti-MRSA coverage) or maintained on BS antibiotics (anti- P. aeruginosa ± anti-MRSA) by therapy day 4 (Figure 1). Mortality, readmission, Clostridium difficile infection, and adverse events from antibiotics were compared between the BS and NS groups. Data were analyzed using logistic generalized estimating equation models and inverse probability of treatment weighting. Results: Of 363 patients with HCAP included, 73 (20%) were switched to an NS regimen. Of 290 patients maintained on anti-PSA BS regimens, 47.6% also continued anti-MRSA therapy. The median age was 72 (IQR, 61–81) and Charlson comorbidity index was 4 (IQR, 2–6) of the entire cohort. Baseline characteristics were similar between BS and NS groups, except more patients had chronic kidney disease in the BS group. On multivariable analysis, no other baseline factors were found to be associated with use of BS antibiotics on day 4. Both total and IV antibiotic duration were longer in the BS group (10 vs. 8 days, P = 0.002, and 4 vs. 3 days, P < 0.001, respectively). On adjusted analysis, there were no differences in patient outcomes (Figure 2). Conclusion: Among patients with HCAP started on empiric MRSA and PSA coverage without microbiological diagnosis, clinical outcomes were similar in patients switched to an NS antibiotic and those maintained on BS antibiotics. Our findings suggest a potential role for antimicrobial stewardship in promoting antibiotic de-escalation in this population. Disclosures: All authors: No reported disclosures.